2006
DOI: 10.1002/ajmg.a.31085
|View full text |Cite
|
Sign up to set email alerts
|

Case of chromosome 6p25 terminal deletion associated with Axenfeld–Rieger syndrome and persistent hyperplastic primary vitreous

Abstract: Axenfeld-Rieger syndrome is inherited in an autosomal dominant pattern and is characterized by anomalies of the anterior segment of the eye and systemic signs including craniofacial dysmorphic features and cardiac defects. The disorder is genetically heterogeneous and one causative gene, FOXC1, is located on chromosome 6p25. Persistent hyperplastic primary vitreous (PHPV) is a congenital ocular disorder in which there is a failure of the normal regression of the primary vitreous and a proliferation of fibrous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Therefore, the derivative 6p in the present child actually designates partial monosomy 6p23 and partial trisomy 10q24 rearranged on 6p. The most of the reported cases had mild to moderate facial or craniofacial dysmorphism coupled with congenital heart defect, ocular anomalies, joint dislocation, or renal defects [1113]. In the present family, the mother was carrying the constitutive balanced translocation and though she had some bilateral depression on the upper segment of her face, she did not have any other significant facial dysmorphism (Figure 1).…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, the derivative 6p in the present child actually designates partial monosomy 6p23 and partial trisomy 10q24 rearranged on 6p. The most of the reported cases had mild to moderate facial or craniofacial dysmorphism coupled with congenital heart defect, ocular anomalies, joint dislocation, or renal defects [1113]. In the present family, the mother was carrying the constitutive balanced translocation and though she had some bilateral depression on the upper segment of her face, she did not have any other significant facial dysmorphism (Figure 1).…”
Section: Discussionmentioning
confidence: 67%
“…Family‐based studies, traditional genetic methods using linkage analysis, and current advances in molecular genetics have identified 2 major ARS genes, PITX2 (4q25, RefSeq NM 000325.5, MIM# 601542) and FOXC1 (6p25, RefSeq NM 001453.2, MIM# 601090), revealing a wide spectrum of mutations, which assists in the molecular diagnosis of the ARS type 1 and type 3, respectively . In addition to small point mutations, several patients with chromosomal deletions at 6p25, including the FOXC1 locus, have been also reported in the literature . As well, deletions within 4q, including PITX2 , have also been reported in ARS patients .…”
Section: The Genetic Basis Of Arsmentioning
confidence: 99%
“…10 In addition to small point mutations, several patients with chromosomal deletions at 6p25, including the FOXC1 locus, have been also reported in the literature. [11][12][13][14][15][16][17][18][19][20][21] As well, deletions within 4q, including PITX2, have also been reported in ARS patients. 22,23 It has also been reported that deletion of 13q14, supported by linkage analyses, can cause ARS type 2; however, mutations in a causative gene are yet to be identified.…”
Section: The Genetic Basis Of Arsmentioning
confidence: 99%
“…Several patients with 6p terminal deletions have been reported [Kume et al, 1998; Law et al, 1998; Nishimura et al, 1998; Baruch and Erickson, 2001; Lehmann et al, 2002; Anderlid et al, 2003; Maclean et al, 2005; Suzuki et al, 2006; Martinez‐Glez et al, 2007; Martinet et al, 2008]. Recently, Gould et al [2004] and Lin et al [2005] summarized the phenotypes of patients with 6p25 deletions, showing that these patients exhibited a recognizable pattern of malformations, namely 6p25 deletion syndrome.…”
Section: Discussionmentioning
confidence: 99%